Evaluation of various carbon materials supported Pt catalyts for aqueous-phase reforming of lignocellulosic biomass hydrolysate - Özsel Kaya, Burçak; Irmak, Sibel; Hasanoglu, Arif; Erbatur, Oktay (Pergamon-Elsevier Science Ltd, 2014)
Currently, under huge pressure from energy demands and environmental problems, much attention is being paid to produce fuel and chemicals from lignocellulosic biomass. In this matter, development of active and also recyclable catalysts are essential. In the present study, various types of carbon supported Pt reforming catalysts were prepared for use in gasification of wheat straw biomass hydrolysate by aqueous-phase reforming. The supports tested were various carbon materials having different surface and structures that were activated carbon (AC), single- and multi-walled carbon nanotubes (SWCNT and MWCNT), superdarco carbon (SDC) and graphene oxide (GO). The catalysts prepared using these supports were evaluated based on gasification yield, carbon amount consumed in the process, sugar alcohols formation and breaking down of organic compounds in the hydrolysate. Compared to other carbon-based supports tested, Pt on activated carbon showed best performance for gasification of biomass hydrolysate. This catalyst was also active on carbon consumption, sugar alcohols production and breaking down soluble organic compounds in the hydrolysate. The second active catalyst, Pt on single-walled carbon nanotube, showed significantly higher activity compared to multi-walled carbon nanotube since large polysaccharides molecules were not able to enter into narrow graphene sheets in multi-walled carbon nanotube to react with Pt deposited inside graphene layers. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Catalyst; Pt; Support; Carbon; APR; Biomass